The Influence of Operational Efficiency, Credit Risk, and Market Risk on the Profitability of State-Owned Banks Listed on the Indonesia Stock Exchange - Magalhaes, Cancio Andhika Irawan; Pandin, Maria Yovia R; Kusmaningtyas, Amiartuti (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of operational efficiency, credit risk, and market risk on the profitability of state-owned banks listed on the Indonesia Stock Exchange during a post-crisis period. Using a quantitative approach and multiple linear regression analysis, the research investigates the relationship between BOPO, NPL, and NIM as independent variables, and ROA as the dependent variable. The findings indicate that all three variables have a significant impact on profitability, both partially and simultaneously. Interestingly, both BOPO and NPL exhibit a positive relationship with ROA, suggesting possible institutional factors or strategic management decisions unique to state-owned banks. Meanwhile, NIM shows a consistent positive effect, reinforcing its role in profit generation. The model satisfies all classical assumptions and demonstrates strong explanatory power. These results offer valuable insights for policymakers and banking practitioners in improving financial performance and managing key financial indicators in the state banking sector.